The Relationship between Knowledge and Attitudes of Students on Menstrual Personal Hygiene in Private Vocational High School Students Napsi'ah Stabat Kab. Langkatin 2022 - Siskawati Amri (Institute of Computer Science (IOCS), 2022)
Adolescence is a period of life where there is psychological exploration to determine self-identity. In the transition period from childhood to adolescence, individuals begin to develop abstract characteristics and self-concepts with personal judgments and standards, but lack the interpretation of social comparisons. Objectives The purpose of this study was to determine the relationship between knowledge and attitudes of adolescent girls on menstrual personal hygiene in private vocational school students Napsi'ah Stabat kab. Langkat in 2022. Factors that cause cataracts are age, physical, chemical, predisposing diseases, genetics, and viral infections during fetal growth. There are various factors that cause cataracts, including: The results of this study are the knowledge of adolescent girls on menstrual personal hygiene in private vocational school students Napsi'ah Stabat kab.